Optimal Inventory Policy With Preservation Technology: A New Dimension For Inventory Management (International Journal of Food and Nutritional Sciences, 2022)
Inventory control is the most important stage of production management. Products include raw materials, equipment, work, finished products, packaged and packaged goods, and general materials. Studying inventory problems of products with storage methods and requirements is very interesting for easy inventory processing and OR research studies. The aim of this study is to add a new dimension to the modeling of inventory control storage technologies at different demand rates and transportation costs. This strategy aims to develop and describe product models of non-standard products with different needs and various real combinations.